HSMNR belongs to the most frequent types of hereditary neuropathy in the Czech Republic and is twice more frequent than HMSNL. Issue 2 (4th March 2016) - Šafka Brožková, D.; Haberlová, J.; Mazanec, R.; Laštůvková, J.; Seeman, P.
Abstract : Hereditary motor and sensory neuropathy type Russe (HMSNR), also called CMT4G, is an autosomal recessive inherited peripheral neuropathy (IPN) caused by a founder mutation in the HK1 gene. HMSNR affects only patients with Roma origin, similar to the better known HMSN type Lom clarified earlier. By testing IPN patients with Roma origin, we realized that HMSNR affects surprisingly many patients in the Czech Republic. HMSNR is one of the most frequent types of IPN in this country and appears to be twice more frequent than HMSNL. Pronounced lower limb atrophies and severe deformities often lead to walking inability in even young patients, but hands are usually only mildly affected even after many years of disease duration. The group of 20 patients with HMSNR presented here is the first report about the prevalence of HMSNR from central Europe. Abstract :